Pragmatic functions of perception verbs (Czech Journal of Multidisciplinary Innovations, 2025)
Perception verbs such as see, hear, feel, taste, and smell frequently extend beyond their literal, sensory meanings to assume a range of pragmatic functions in discourse. This paper explores how these verbs are used in English to convey evidentiality, epistemic stance, and politeness strategies. Drawing on insights from both international scholarship (Sweetser, 1990; Taboada, 2011) and Uzbek researchers (Ganieva, 2021; Rahimova, 2019), this study provides examples from authentic English data illustrating the ways in which perception verbs facilitate negotiation of meaning, manage interpersonal relationships, and position speakers’ authority or subjectivity within discourse